Seagrass spatial distribution based on density in the waters of Tunda Island, Banten. Issue 1 (March 2021) - Sugianti, Y; Rusli, M; Mujiyanto,; Indrayanto, F R; Khalifa, M A
Abstract: One of the coastal ecosystems on Tunda island is the seagrass ecosystem, which functions as a primary producer, breakwater, spawning ground, nursery ground, and feeding ground for fish. Mining of sea sand around this island can potentially result in environmental degradation. The purpose of this study was to determine the type, density and percentage of seagrass cover as well as the influence of environmental factors on seagrass species and their spatial distribution. The research was conducted in July 2019 at 14 stations around the island. The results showed that the species composition of seagrass from the stations on Tunda Island consisted of 6 species with a similarity index of more than 75% except at stations 6, 7, 10 and 13. Correspondence analysis shows that the spatial distribution of stations is different and is influenced by habitat characteristics. Thalassia hemprichii dominates the entire station, followed by Enhalus acoroides 6 stations, Halophila ovalis 4 stations, while Cymodocea rotundata is only found at 2 stations, and Cymodocea serrulata at 1 station. The distribution and species composition also shows that the seagrass beds in Tunda Island are in a healthy category.